2018
DOI: 10.1007/978-981-10-7230-7_1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HSV Glycoproteins in Mediating Cell Entry

Abstract: The successful entry of herpes simplex virus (HSV) into a cell is a complex process requiring the interaction of several surface viral glycoproteins with host cell receptors. These viral glycoproteins are currently thought to work sequentially to trigger fusogenic activity, but the process is complicated by the fact that each glycoprotein is known to interact with a range of target cell surface receptor molecules. The glycoproteins concerned are gB, gD, and gH/gL, with at least four host cell receptor molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…Specifically, we applied a branch-site test, which is well-suited to identify episodic positive selection -i.e., selection events that occurred on a specific branch of a phylogeny. Among core genes, we found evidence of episodic positive selection in three glycoproteins, namely gB, gM, and gH, all of which contribute to virus cell entry via membrane fusion (Arii and Kawaguchi, 2018;El Kasmi and Lippé, 2015). For gB and gH we found that some of the positively selected sites map to antigenic determinants, suggesting that the host adaptive immune response represents the underlying selective pressure.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, we applied a branch-site test, which is well-suited to identify episodic positive selection -i.e., selection events that occurred on a specific branch of a phylogeny. Among core genes, we found evidence of episodic positive selection in three glycoproteins, namely gB, gM, and gH, all of which contribute to virus cell entry via membrane fusion (Arii and Kawaguchi, 2018;El Kasmi and Lippé, 2015). For gB and gH we found that some of the positively selected sites map to antigenic determinants, suggesting that the host adaptive immune response represents the underlying selective pressure.…”
Section: Discussionmentioning
confidence: 85%
“…Second, both the interplay of viral and cellular components at the plasma membrane in initiating entry mechanisms, and the subsequent downstream signaling or intracellular events, have been investigated in depth at the biological, cellular, biochemical, molecular and structural levels. HSV has a set of four envelope glycoproteins essential for virus entry: gD (involved in specific receptor recognition and binding, and the triggering of the fusogenic signal to downstream effectors), gB (a class III fusogenic glycoprotein which executes fusion), and the heterodimer gH/gL (partnering gB to execute fusion, and lacking any similarity with any other fusion protein) [3,[107][108][109][110]. Recently, insights into additional gB domains spatially distant from the fusion loops have come from structural studies on the related alpha-herpesvirus varicella zoster virus (VZV) [111].…”
Section: Tropism Retargeted Unattenuated Ohsvsmentioning
confidence: 99%
“…These glycoproteins exploit a wide array of natural receptors for target cell recognition and fusion execution. Thus HVEM/HveA, Nectin-1/HveC and 3-OS HS are receptors for gD, PILRα, MAG and NMHC-IIA and B are bound by gB, and gH/gL interact with integrins [5,109,[112][113][114][115]. This multipartite system allows the virus to penetrate via two different pathways-by fusion at the plasma membrane or by endocytosis [4,[116][117][118].…”
Section: Tropism Retargeted Unattenuated Ohsvsmentioning
confidence: 99%
“…When nucleocapsid is transported to the secondary envelope loci that associate with the Golgi apparatus, VP16 cannot only bind to outer tegument proteins of the outer tegument-envelope complex but also directly bind to some glycoproteins of the complex (Figure 4). After contact with the glycoproteins, the produced nucleocapsids can effectively bud in vesicles to complete secondary envelopment; this is because the glycoproteins can identify specific receptors on the membrane and promote the penetration of virions (Arii and Kawaguchi, 2018;White et al, 2020).…”
Section: The Mechanism Of Vp16 Effects On Secondary Envelopmentmentioning
confidence: 99%